CAN MONTH OF BIRTH AND UV RADIATION AFFECT MULTIPLE SCLEROSIS RISK IN PROVINCES OF IRAN? - Fatemeh Naddafi; kazem Naddafi; Mohammad Sadegh Hassanvand (Journal of Air Pollution and Health, 2015)
Introduction: Multiple sclerosis (MS) is an inflammatory autoimmune disease of the central nervous system that affects women more than men. Environmental factors such as sunlight, through Ultraviolet (UV) radiation can have a pivotal role in MS prevalence. MS is more common in mid latitude temperate climatic areas, such as the northern United States, southern Canada and northern Europe. It has been shown that there is a low risk of MS in the hot, moist and extremely dry equatorial zone, and vice versa. Materials and methods: In this study, UV radiation data as UV index were collected from a geographic database provided by The Environmental Health Information System of Islamic Republic of Iran. The monthly average UV index during pregnancy leading to 15th of each month has been used to create GIS maps by using ArcGIS 9.3. Results: In this paper, It was focused on the potential effect of UV radiation on MS prevalence. It was found that there is a low maternal exposure to UV radiation in people born in April and May in all provinces of Iran and they can be more susceptible to MS. Conclusions: This study shows that Iranian high exposure to UV radiation can reduce the risk of MS. It was indicated that Iran is a low risk area for MS and people born in April and May are more susceptible to MS due to low exposure to UV radiation. Thus, birth months could be considered as an important factor in MS prevalence.